Soviet Global Modernity and the Conception of Globality-Locality in Soviet Lithuania - Leonavičius, Vylius; Keturakis, Saulius (Sociologija. Mintis ir veiksmas, 2002)
This paper has several analytical perspectives. The subject of paper is the social and cultural processes of the former Soviet society. The analysis depends upon the ideas of the modernization theory (Z. Bauman, A. Giddens, R. Inglehart, S. Hall). It is argued that the former Soviet society could be analyzed as the specific case of modern society. On the one hand, it could be characterized by the features of the modern society such as industrialization, urbanization, rationalization, bureaucratization. On the other one, Soviet society lacked several features, which are the important features that describe modern societies (the priority of individual, civic participation). The paper suggests that the general opposition soviet-national could be changed by opposition global-local and analyzed from the theoretical perspective of global modernity. In addition, the interaction between soviet and national is analyzed by the Dumont’s hierarchical complementary principle. From this point of view, the Soviet nation was higher in comparison with any other national group in the Soviet Union. But since the Russians were identified as Soviet nation they were a part and a whole at the same time. The decisions and choices of individuals were constructed by this general opposition. For this analysis the concept of discursive practices (M. Foucault) is applied.